Vascular surgery: What increases the flow of students to the speciality?. (June 2019) - Turki, Mohammed Adil A; Zargaran, Alexander; Murtaza, Aasim; Thomas, Amal; Spiers, Harry; Gill, Moneet; Aggarwal, Shaurya; Turki, Sarah; Zargaran, David
Objectives: Vascular surgery is in increasing demand due to the higher prevalence of cardiovascular disease in the general population. Meanwhile, applications to join the speciality have been in decline in the last few years. St George's Surgical Society held a one-day conference to expose undergraduates to the speciality in the hope that this will inspire more undergraduates to pursue it as a career. Methods: The conference consisted of introductory lectures delivered by a consultant vascular surgeon, followed by practical skills workshops simulating aortic anastomosis on porcine aortas. Pre-course and post-course questionnaires assessed positive and negative perceptions of vascular surgery, knowledge of and self-reported confidence in practical surgical skills and utility of the course in their decision to potentially pursue a career in vascular surgery. Results: There was a significant increase of 27% ( p  = 0.03) in the positive perception that vascular surgery includes a diverse range of procedures and subspecialties. Attendees reported a 27% significant increase ( p  = 0.02) in the perception that vascular surgery had a wide array of opportunity for academic/research work. Finally, there was an 18% decrease ( p  = 0.03) in the negative perception that vascular surgery is somehow female-unfriendly or discriminatory against females. There was also a significant rise in both interest (33%) and understanding (73%) of vascular surgery. Conclusions: A one-day conference can significantly impact students' perception especially when there is a lack of exposure within the undergraduate curriculum. This course helped to increase positive perception and dispute negative misconceptions about the speciality. The simulation workshops held at this conference increased students' confidence and awareness of relevant surgical skills. This conference provided a unique experience that positively impacted and inspired students and thus served as an important supplement to core medical curriculum.